2011
DOI: 10.1016/j.jus.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Enthesitis of the direct tendon of the rectus femoris muscle in a professional volleyball player: A case report

Abstract: Enthesitis of the direct tendon of the rectus femoris muscle is a rare pathology which mainly affects professional athletes, and it is caused by overuse and repetitive microtrauma. Athletic jumping and kicking exert a great stress on the direct tendon of the rectus femoris muscle, and volleyball and football players are therefore most frequently affected. Enthesitis may occur suddenly causing pain and functional impairment possibly associated with partial or complete tendon injuries, or it may be a chronic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…No differences were found in the HAGOS values between these groups among the athletes with a history of groin pain during the previous season. Bortolotto et al [4] reported that the hip and the rectus femoris are commonly affected in volleyball professional athletes. The quadriceps muscle is involved in hip and knee joints and it is overstretched in the landing phase of the jump when the hip is extended and the knee is flexed; the muscle is therefore contracted and extended, and this increases the risk both of acute injury and of microtrauma leading to degenerative changes [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No differences were found in the HAGOS values between these groups among the athletes with a history of groin pain during the previous season. Bortolotto et al [4] reported that the hip and the rectus femoris are commonly affected in volleyball professional athletes. The quadriceps muscle is involved in hip and knee joints and it is overstretched in the landing phase of the jump when the hip is extended and the knee is flexed; the muscle is therefore contracted and extended, and this increases the risk both of acute injury and of microtrauma leading to degenerative changes [31].…”
Section: Discussionmentioning
confidence: 99%
“…A group of international experts on the topic [6] stated that the available literature is mainly based on heterogeneous studies with low methodological quality. As far as we know, there are few studies on groin pain in team sport athletes such as basketball [9], volleyball [4], ice hockey [53, 54] and water polo [42] other than soccer [2, 10, 12, 17, 27, 28, 42–44, 46, 51]. Traditional epidemiological sports injury research on groin injuries has mainly focused on time loss injuries [51], defined as injuries resulting in a player not being able to participate fully in soccer training or match play [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is mostly isolated but association with MTJ strain has been previously described [27]. Apatite calcifications appear as a convex hyperechoic mass with posterior acoustic shadow and usually occur without previous history of trauma (Fig.…”
Section: Tendinopathiesmentioning
confidence: 95%
“…Calcifications may also be related to hydroxyapatite deposition, and typically involve the dRF . Entheseal calcifications due to chronic microtraumas may also be seen . The examiner should remember that the use of excessive real‐time compounding affects the detection of calcifications as it masks their posterior shadowing.…”
Section: Pathologic Findingsmentioning
confidence: 99%